Identification and Analysis of Long Non-coding RNAs in Leuciscus waleckii Adapted to Highly Alkaline Conditions - Zhao, Xue Fei; Liang, Li Qun; Liew, Hon Jung; Chang, Yu Mei; Sun, Bo; Wang, Shuang Yi; Mi, Bo Han; Zhang, Li Min (Frontiers in Physiology, 2021)
Leuciscus waleckii is a freshwater fish that is known to inhabit the Dali Nor Lake, Inner Mongolia, China. The water in this lake has an HCO3–/CO32– concentration of 54 mM (pH 9.6) and a salinity of 0.6‰. The physiological mechanisms that allow this fish to tolerate these saline/alkaline conditions have yet to be elucidated. Transcriptional component analysis has shown that the expression levels of a large number of genes involved in the pathways responsible for osmo-ionoregulation and arachidonic acid metabolism pathway expression change significantly (p < 0.05) during the regulation of acid–base balance under high alkaline stress. In this study, we investigated the role of long non-coding RNAs (lncRNAs) during adaptation to high alkaline conditions. Fish were challenged to an NaHCO3-adjusted alkalinity of 0 mM, 30 mM (pH 9.44 ± 0.08), and 50 mM (pH 9.55 ± 0.06) for 20 days in the laboratory. Gill and kidney tissues were then collected for high-throughput sequencing assays. A total of 159 million clean reads were obtained by high-throughput sequencing, and 41,248 lncRNA transcripts were identified. Of these, the mean number of exons and the mean length of the lncRNA transcripts were 4.8 and 2,079 bp, respectively. Based on the analysis of differential lncRNA transcript expression, a total of 5,244 and 6,571 lncRNA transcripts were found to be differentially expressed in the gills and kidneys, respectively. Results derived from Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis of the coding genes were correlated with the lncRNA expression profiles. GO analysis showed that many lncRNAs were enriched in the following processes: “transporter activity,” “response to stimulus,” and “binding.” KEGG analysis further revealed that metabolic pathways were significantly enriched. A random selection of 16 lncRNA transcripts was tested by RT-qPCR; these results were consistent with our sequencing results. We found that a large number of genes, with the same expression profiles as those with differentially expressed lncRNAs, were associated with the regulation of acid–base balance, ion transport, and the excretion of ammonia and nitrogen. Collectively, our data indicate that lncRNA-regulated gene expression plays an important role in the process of adaptation to high alkaline conditions in L. waleckii.